Transitivity Analysis of Colombian President Juan Manuel Santos’ Nobel Peace Prize Lecture - Moncada Linares, Sthephanny; Zhi-Ying, Xin (International Journal of Language and Literary Studies, 2020)
The present document will offer an analysis of the Nobel Peace Prize acceptance lecture delivered by the former Colombian President, Juan Manuel Santos, from the fundaments of the transitivity system provided by the Systemic Functional Grammar theory. To attain this goal, a quantitative and qualitative research method approach was applied. Findings indicated that among the six transitivity process types, the material processes (54% - 205 realizations) dominate the speech whereas the verbal, existential, and behavioral processes are relatively low all together representing an overall occurrence of 10% (41 realizations). This reveals that the speaker’s main goal is to emphasize the actions that led to consolidating the Colombian peace process, placing him as the core actor of this achievement. Furthermore, by employing a narrative thread that connects the past, the present, and the future time, he can demonstrate to the world his capability as a governor who deserves to be awarded the Nobel Prize.